Effect of chemotherapy on the uterus of young adult cancer survivors - Deepika Garg, M.D; Matthew Hodgman; Sydney Reil; Lesley Lomo, M.D; Kenneth Ivan Aston, Ph.D; Jonathon Hill, Ph.D; Erica Johnstone, M.D; Tim Jenkins, Ph.D; Joseph M. Letourneau, M.D (Elsevier, 2022)
Objective: To investigate the impact of chemotherapy on the uterus. Design: Cross-sectional pilot study. Setting: Single university fertility clinic. Patient(s): Twelve patients with a history of alkylating agent chemotherapy exposure after Hodgkin lymphoma (cancer) vs. 12 normally menstruating women (controls). Intervention(s): The inclusion criteria were age of 18-45 years and consent for endometrial biopsy. The exclusion criteria were the absence of the uterus, completed pelvic radiation, uterine or cervical cancer, and metastatic cancer. Each participant underwent endometrial biopsy and pelvic ultrasound. All study visits were conducted in the late proliferative phase of the menstrual cycle. Main Outcome Measure(s): Uterine volume, blood flow, endometrial thickness, histology, deoxyribonucleic acid methylation pattern, and relative ribonucleic acid (RNA) expression level during the same phase of the menstrual cycle. Result(s): In the study group, visits were conducted at a median of 31.5 (13.5-42.5) months after chemotherapy. The median uterine volume among cancer survivors was 36 (11.3-67) cm3, and that of the general population controls was 39 (13-54) cm3. On histologic examination, there were no cytologic or architectural atypia. The RNA-sequencing analysis revealed poor clustering of both control and treatment samples. However, we identified 3 differentially expressed genes on RNA-sequencing, but there was no concordance found among the differentially expressed genes and deoxyribonucleic acid methylation changes suggesting most likely false-positive results. Conclusion(s): Approximately 2.5 years after chemotherapy, a time at which several survivors of Hodgkin lymphoma may resume family-building, endometrial thickness and endometrial histology were not significantly affected by a history of alkylating agent chemotherapy exposure.